A systematic review of models of care for polycystic ovary syndrome highlights the gap in the literature, especially in developing countries - Melson, Eka; Davitadze, Meri; Malhotra, Kashish; , PCOS SEva working group; Mousa, Aya; Teede, Helena; Boivin, Jacky; Thondan, Mala; Tay, Chau Thien; Kempegowda, Punith (Frontiers in Endocrinology, 2023)
Introduction: To identify available polycystic ovary syndrome (PCOS) models of care (MoC) and describe their characteristics and alignment with the international PCOS guideline. Methods: OVID MEDLINE, All EBM, PsycINFO, EMBASE, and CINAHL were searched from inception until 11 July 2022. Any study with a description of a PCOS MoC was included. Non-evidence-based guidelines, abstracts, study protocols, and clinical trial registrations were excluded. We also excluded MoCs delivered in research settings to minimize care bias. Meta-analysis was not performed due to heterogeneity across MoCs. We describe and evaluate each MoC based on the recommendations made by the international evidence-based guideline for assessing and managing PCOS. Results: Of 3671 articles, six articles describing five MoCs were included in our systematic review. All MoCs described a multidisciplinary approach including an endocrinologist, dietitian, gynaecologist, psychologist, dermatologist, etc. Three MoCs described all aspects of PCOS care aligning with the international guideline recommendations. These include providing education on long-term risks, lifestyle interventions, screening, and management of emotional well-being, cardiometabolic diseases, and dermatological and reproductive elements of PCOS. Three MoCs evaluated patients’ and healthcare professionals’ satisfaction, with generally positive findings. Only one MoC explored the impact of their service on patients’ health outcomes and showed improvement in BMI. Conclusions: There is limited literature describing PCOS MoCs in routine practice. Future research should explore developing cost-effective co-created multidisciplinary PCOS MoCs globally. This may be facilitated by the exchange of best practices between institutions with an established MoC and those who are interested in setting up one.